Single or paired increase of total alkalinity and hardness of water for cultivation of Nile tilapia juveniles, Oreochromis niloticus - doi: 10.4025/actascitechnol.v34i2.12003 - Cavalcante, Davi de Holanda; Silva, Suzete Roberta da; Pinheiro, Paloma Damasceno; Akao, Michael Masaki Freitas; Sá, Marcelo Vinícius do Carmo e (Acta Scientiarum. Technology, 2011)
The present work aimed at evaluating the effects of single or paired increase of water´s total alkalinity (TA) and total hardness (TH) on the performance of Nile tilapia juveniles´ growth and culture water quality. Twenty five 25-L outdoor polyethylene aquaria were used to hold experimental fish (0.82 Â± 0.06 g; 10 fish per aquarium) for 6 weeks. There were two conditions of TA (low or high) and of TH (moderate or high) in the culture water, obtained by the application of different salts (CaCO3, Na2CO3 and CaSO4) upon a previously acidified water, all at the same rate. Water quality and growth performance variables were observed in each replicate. The acidification of the supply water with HCl has resulted in significantly lower final body weight (p < 0.05). Except for the Na2CO3, growth performance of tilapia has improved significantly after CaCO3 liming or CaSO4 application (p < 0.05) and no significant difference was detected between these last two fish groups (p > 0.05). It was concluded that beyond a minimum level of TA (â‰¥ 20 mg L-1 CaCO3) and TH (â‰¥ 20 mg L-1 CaCO3), it is also important that fish culture waters have a TH/TA ratio higher than 1.